Cognitive enhancement: a brief overview - Kim Outhoff (South African Family Practice)
Cognitive enhancement involves the non-medical use of illicit and/or prescription drugs, such as agents prescribed for attention deficit/hyperactive disorder (ADHD) and narcolepsy, usually in order to stay awake and to counteract fatigue and loss of concentration, generally in the context of high workload and stress. Growing interest in taking prescription stimulant drugs for non-licensed purposes to improve academic, work and sporting performance has raised medical, ethical and regulatory issues.